Perbandingan Kinerja Marshall Pada Campuran Aspal AC-WC Menggunakan Plastik Polypropilene (PP) Dan Plastik High Density Polyethylene (HDPE) - T, Nurfadila; Mustakim, Mustakim; Fadly, Imam (Sultra Civil Engineering Journal (SCiEJ), 2024)
According to the Ministry of Environment and Forestry, Indonesian people produce 0.8 kg of waste per person per day, of which 15% is plastic waste or equivalent to 189,444,000 tons of waste per day 8, Therefore, the amount of waste must be proportional to the proportion of waste processed and the rest must not be disposed of and pollute the environment. The types of plastics used in this study were Polypropylene (PP) Plastic and High Density Polyethylene (HDPE) Plastic. The purpose of this study was Determination of Melshell performance in AC- WC asphalt mixture without the addition of polypropylene (PP) plastic and high density polyethylene plastic (HDPE). The research method used was experimental with variations of 2%, 4%, and 6%, from the weight of KAO asphalt. Marshall comparison results AC-WC asphalt using polypropylene (PP) and high density polyethylene (HDPE) resins, with only VMA and MQ stable values meeting the 2018 Development Specifications while VFA, VIM and FLOW do not meet the specifications